An investigation on droplet transfer for bypass-current wire-heating PAW. (May 2021) - Miao, Yugang; Yin, Chenhao; Wei, Chao; Li, Chunwang
Abstract: In the process of plasma arc welding (PAW), the thermodynamic behavior of droplets has an important influence on the control of shape and performance. On the basis of plasma arc welding, the method of bypass-current wire-heating PAW is further developed. The wire is sent directly to the center of plasma arc, and a part of plasma current is separated through the welding wire, which not only reduces the heat input to the base metal, but also improves the melting efficiency of welding wire. The test was carried out with the H08Mn2Si steel wire with a diameter of 1.2 mm as the test material, and the base metal was Q235 low carbon steel plate. The effect of different process parameters on the droplet transfer form was studied, and the threshold conditions for the change of droplet transfer form were revealed. The results show that the force condition on the droplet can be changed by using the coordinated control method of the main/bypass current, and the droplet transfer form can be changed from bridging transfer to drop spray transfer and fluid spray transfer. The accurate control of droplet transfer form can be realized to achieve a stable molten pool state, then the forming quality and accuracy of the weld bead can be improved to achieve the purpose of using this method to achieve precise additive manufacturing.